Effectuation Logic and Early Innovation Success: The Moderating Effect of Customer Co‐creation. (6th October 2021) - Ko, Guihan; Roberts, Deborah. L.; Perks, Helen; Candi, Marina
Abstract: This research examines whether and how customer co‐creation activities moderate the relationship between effectuation logic and performance in the early stage of the innovation process. Effectuation logic is a promising decision‐making logic for innovation success, but the tools that help translate this approach into innovation performance are under‐researched. Three key dimensions of effectuation logic are examined: means‐driven, partnerships and control. The results of a large‐scale survey‐based study indicate a varied and nuanced role of co‐creation as a means to enhance the contribution of effectuation logic to early innovation success. This research helps increase our understanding of the often abstract principles of effectuation logic by examining its manifestation within the context of innovation and by showing how specific firm practices, here customer co‐creation activities, can accentuate the contribution of effectuation logic to early innovation performance.